Peran Guru dalam Perencanaan Pembelajaran Berbasis Kurikulum Merdeka di SD Negeri 060874 Medan - Sukarman Purba; Sahala Siallagan; Parlaungan Lubis (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2025)
This study aims to analyze the role of teachers in lesson planning based on the Independent Curriculum (Kurikulum Merdeka) at SD Negeri 060874 Medan. The Independent Curriculum emphasizes autonomy, flexibility, and the development of students’ competencies according to their potential and interests. In this context, teachers play a strategic role as designers, implementers, and developers of meaningful learning. This research employs a descriptive quantitative approach with a population of 22 teachers. Data were collected through questionnaires and analyzed using descriptive statistics to determine teachers’ involvement in the stages of needs analysis, learning objective formulation, strategy selection, and lesson plan evaluation. The results show that the teachers’ role in lesson planning based on the Independent Curriculum is in the very good category, with an average score of 85%. Teachers demonstrate the ability to adapt lesson plans to students’ characteristics and the achievement of the Pancasila Student Profile. These findings indicate that the implementation of the Independent Curriculum at SD Negeri 060874 Medan has been effective due to teachers’ professional readiness in designing adaptive and contextual learning processes.